Episodic Mapping Strategy: Structuring Students’ Reading Comprehension - Melgis Dilkawaty Pratama; Mia Diana Binti Idris (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This research investigated the effect of Episodic Mapping strategy on students’ reading comprehension in narrative text. It examined the difference of students’ reading comprehension before and after using the Episodic Mapping strategy. Quasi-experiment with nonequivalent control group was used as design of this research. 70 students of a Senior High School in Indonesia were selected by using cluster random sampling. The data was obtained from multiple choice test and analyzed by Independent sample t test. As results, the experimental group performed better than the other at posttest stage. In addition, students at experimental group developed their reading comprehension by extracting text structure. Hence, Episoding mapping strategy significantly reinforces students’ reading comprehension.